A high-resolution map of non-crossover events reveals impacts of genetic diversity on mammalian meiotic recombination - Ran Li (Nature Portfolio, 2019)
During meiotic recombination, genetic information is transferred or exchanged between parental chromosome copies. Using a large hybrid mouse pedigree, the authors generated high-resolution maps of these transfer/exchange events and discovered new properties governing their processing and resolution.